Sociology of youth in Ukraine yesterday, today, tomorrow: photo sketch = Socjologia młodzieży na Ukrainie wczoraj, dziś, jutro: fotoszkic - Sokuryanska, Ludmila G.; Golikov, Alexander S. (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article reflects on the emergence and development of the sociology of youth in Ukraine over the past decade. Attention is drawn above all to the empirical nature of this branch of sociological knowledge and its reference to the analysis of specific youth problems. The connections of the sociology of youth with other middle-range sociological theories, primarily the sociology of education, are revealed. A detailed comprehension of the experience of the sociology of youth development over the past decade in Ukraine is provided.
Keywords: sociology of youth; youth; sociological reflection; Ukrainian journals; Ukrainian sociology; socjologia młodzieży; młodzież; refleksja socjologiczna; czasopisma ukraińskie; socjologia ukraińska